Increased utilisation of eye disorder-related ambulatory medical services prior to the diagnosis of Sjögren's syndrome in female patients: a longitudinal population-based study in Taiwan - Lu, Ming-Chi (BMJ Publishing Group, 2014)
OBJECTIVES: To investigate the utilisation of eye disorder-related ambulatory medical services prior to the diagnosis of primary Sjögren's syndrome in female Taiwanese patients. DESIGN: A nationwide, population-based case–control study. SETTING: Taiwan's National Health Insurance Research Database. PARTICIPANTS: A total of 347 patients with a diagnosis of primary Sjögren's syndrome from 2005 to 2010 and 1735 controls frequency matched on 10-year age interval and index year were identified from Taiwan's National Health Insurance Research Database. Diagnoses of eye disorder (International Classification of Diseases, Ninth Revision, clinical modification (ICD-9-CM) codes from 360 to 370) were retrospectively screened to 1997. MAIN OUTCOME MEASURE: The utilisation of eye disorder-related medical service over different intervals prior to diagnosis of Sjögren's syndrome between cases and controls were compared using generalised estimating equations with negative binomial distribution and log link function. RESULTS: A significantly higher proportion of patients with Sjögren's syndrome (7.5%) utilised eye disorder-related ambulatory medical services over an 8-year interval prior to the diagnosis of the disease compared with controls (4.8%). The annual frequency of utilisation of eye disorder-related ambulatory medical services increased significantly faster when closer to the index date in patients with Sjögren's syndrome compared with controls (interaction effect, p=0.010). Subgroup analyses indicated that the changes over time in the utilisation of services related to disorders of lacrimal system (interaction effect, p=0.019) and conjunctiva (interaction effect, p=0.066) were significantly greater in patients with Sjögren's syndrome compared with controls. CONCLUSIONS: An increase in the utilisation of eye disorder-related ambulatory medical services was observed in patients with Sjögren's syndrome several years prior to the diagnosis of the disease. General practitioners and ophthalmologists can play an important role by including Sjögren's syndrome in the diagnostic evaluation of their patients afflicted with relevant symptoms.